Metabolic syndrome and its components as criteria for evaluating the efficiency of hypertension disease treatment - B. B. Pinkhasov; V. G. Selyatitskaya; Yu. V. Lutov; D. A. Deev (Бюллетень сибирской медицины)
Purpose of the study was to evaluate the effectiveness of complex treatment of essential hypertension based on the definition of risk of development, frequency and severity of metabolic syndrome (MS) and its components before and after treatment in male patients of the therapeutic clinic.Materials and methods. The study included 123 patients hospitalized with a main diagnosis of hypertension. In addition to the main examination, anthropometric, instrumental and hormonal-biochemical examination was additionally carried out. A point assessment of deviation degree and additional components of MS from reference was defined. In accordance with the received sum of points each patient was assigned a specific stratification category in relation to MS: lack of risk of development, existence of low, moderate or high risk of development and also light, medium or heavy severity of MS. Repeated examination was carried out in 14 days from initiation of treatment. The effectiveness of treatment was estimated as significant improvement, improvement, without change, deterioration, or significant deterioration depending on change of sum of points.Results. Before the start of treatment, 22.8% of the examined patients had a moderate or high risk of developing MS, and 77.2% had MS of varying degrees of severity. After 14 days the number of patients with MS decreased by 14.6%, and the number of patients with risk of its development increased to 37.4%. In 14 days the number of patients with MS decreased by 14.6%, and the number of patients with risk of his development increased to 37.4%. Among all components of the MS, the greatest number of cases of improvement was noted for hypertension. Significant improvement from the carried-out therapy was revealed in 17.9%, improvement in 39.0%, lack of changes in 37.4% and deterioration in 5.7% of patients.Conclusion. The employment of the method of Point assessment of degree of risk development and severity of MS, as a cluster of risk factors for the development of cardiovascular diseases, in patients with essential hypertension allowed the estimation of efficiency of the carried-out therapy and the individualization of a treatment regimen.